L’embouchure de l'Amazone, macro-frontière géomorphologique : enseignements de 30 années de recherches franco-brésiliennes sur les systèmes côtiers amazoniens (2e partie) - M. T. R. C. Prost; J-F. Faure; C. Charron; H.V. Borges; V. F. Santos; A.C. Mendes; A. Gardel (Confins, 2018)
The Mouth of the Amazon River, considered to be the largest river on Earth, is a geomorphological macro-frontier between two coastal blocks : the Guiana Shield coastal plain (from Amapa to Venezuela) and the North Brazil block (Pará/Maranhão). It also constitutes a vast geological domain that links the Amapa Platform, the Marajo Basin and the Pará/Maranhão Platform. This Paper brings a synthetic view on this coastal compartment. It refers to a large number of multidisciplinary scientific results, and to remote sensing breakthroughs in environmental monitoring. The main purpose of the Paper is to enlight the role of the Mouth as a threshold in regional and local dinamics and processes. The geomorphological analysis relies on a taxonomy of facts and on dialectics between types and individuals. Final considerations are focused on environmental indicators and on current trends in coastal evolution in the Amazon.